How do you simply sec(-x)?

2 Answers
Feb 18, 2018

Answer:

#sec(-x)=1/cos(x)=sec(x)#

Explanation:

You probably meant "simplify".
The secant function is only the inverse of the cosine function.
So #sec (x) = 1/cos(x)#.

Now, the cosine function is said to be an "even" function.
That is, if you put #-x# instead of #x#, you still get the same thing.
So, #cos (-x) = cos(x)#

Therefore,
#sec(-x)=1/cos(-x)=1/cos(x)=sec(x)#

I hope this helps!

Feb 18, 2018

Answer:

Since secant is an even function f(-x)= f(x), so therefore to simplify it, it's just sec(x)

Explanation:

Sec and Cos are even functions, meaning they have y-axis symmetry
Tan, Cot, Sin, Csc are odd functions, meaning that they have origin symmetry and f(-x) in this case is equal to -f(x).